APPLICATION OF GUIDED INQUIRY MODEL ASSISTED BY AUDIO-VISUAL MEDIA TO IMPROVE INQUIRY SKILLS IN SCIENCE LEARNING - Siti Khoiriyah; Ahmad Khoiri (Program Studi Pendidikan IPA FIP Universitas Hasyim Asy'ari, 2024)
This study examines the improvement of students' inquiry skills facilitated through the implementation of a guided inquiry learning strategy accompanied by the use of audiovisual media, and measures the magnitude of the improvement of these skills after the implementation of this strategy. This study adopted a nonequivalent control group design as a type of quasi-experiment. All students in grade VIII at SMP Negeri 1 Garung became the target population. The selected sample subjects were VIII C class as the treatment group, and VIII A class as the comparison group with non-random sample selection method. The instruments utilized in this research are test devices, observation sheets, and documentation. The results of the analysis showed that the inquiry skills of students who received a guided inquiry strategy accompanied by audiovisual media had a higher average than those who only received a guided inquiry strategy without audiovisual media. The results of the comparison test of the means of two independent groups with a significance level of 5% resulted in a significance value of 0.000 <0.05, so ha is accepted while ho is rejected. Testing with the N-Gain metric showed that the average score of the treatment group was 0.75, which was in the high category, while the average score of the comparison group was 0.68, which was in the medium category. Based on this analysis, it can be seen that the guided inquiry strategy with audiovisual media support is effective in improving students' inquiry skills.